Segment‐Scale Seismicity of the Ultraslow Spreading Knipovich Ridge - Meier, Michaela; Schlindwein, Vera; Scholz, John‐Robert; Geils, Jonah; Schmidt‐Aursch, Mechita C.; Krüger, Frank; Czuba, Wojciech; Janik, Tomasz (FID GEO, 2021)
Ultraslow spreading ridges form the slowest divergent plate boundaries and exhibit distinct spreading processes in volcanically active magmatic sections and intervening amagmatic sections. Local seismicity studies of ultraslow spreading ridges until now cover only parts of segments and give insight into spreading processes at confined locations. Here, we present a microseismicity data set that allows to study spreading processes on the scale of entire segments. Our network of 26 ocean bottom seismometers covered around 160 km along axis of the ultraslow spreading Knipovich Ridge in the Greenland Sea and recorded earthquakes for a period of about 1 year. We find seismicity varying distinctly along‐axis. The maximum earthquake depths shallow over distances of 70 km toward the Logachev volcanic center. Here, swarm activity occurs in an otherwise aseismic zone. Melts may thus be guided along the subparallel topography of the lithosphere‐asthenosphere boundary toward major volcanic centers explaining the uneven along‐axis melt distribution typical for ultraslow ridges. Absence of shallow seismicity in the upper 8 km of the lithosphere with a band of deep seismicity underneath offsets presumably melt‐poor regions from magma richer sections. Aseismic deformation in these regions may indicate weakening of mantle rocks by alteration. We do not find obvious indications for major detachment faulting that characterizes magma‐poor spreading at some ultraslow spreading segments. The highly oblique spreading of Knipovich Ridge may be the reason for a fine‐scale segmentation of the seismic activity with zones of weak seismicity possibly indicating transform motion on short obliquely oriented faults. : Plain Language Summary: At mid‐ocean spreading ridges, tectonic plates drift apart and new seafloor is built by upwelling magma. The slowest spreading ridges do not receive enough magma to build new seafloor along the entire ridge. Rather, they show widely spaced volcanic centers with magma‐poor areas in‐between. The study of small earthquakes with seismometers placed on the seafloor has greatly helped to understand how new seafloor forms. Since such studies require substantial logistic effort, only confined ridge sections have been studied and spreading processes operating at segment‐scale remain poorly understood. In this study, we present for the first time observations of earthquakes covering several segments and one major volcanic center along the Knipovich Ridge in the Greenland Sea. Underneath the volcano, earthquake swarms and a gap in seismicity indicate recent magmatic activity. The maximum depth of earthquakes marks the thickness of the mechanically strong lithosphere. It shallows over 70 km toward the volcano such that melts can be channeled over large distances to the prominent volcanoes. Magma‐poor regions have deep earthquakes but do not show earthquake activity in the upper 8 km. We suppose that water reacts with the mantle rocks that become too weak to break in earthquakes. : Key Points: Magma‐poor sections are distinguished from magma‐rich sections by deeper hypocenters and an absence of shallow seismicity. Shallowing maximum earthquake depths over distances of 70 km suggest along‐axis melt focusing toward major volcanic centers. Major detachment faults on the highly oblique spreading Knipovich Ridge were not obvious in the observed seismicity. : Deutsche Forschungsgemeinschaft (DFG) http://dx.doi.org/10.13039/501100001659 : Helmholtz Excellence Network POSY at the Alfred Wegener Institute : Ministry of Science and Higher Education of Poland